1973
DOI: 10.1136/bmj.1.5851.458
|View full text |Cite
|
Sign up to set email alerts
|

Amodiaquine-induced Agranulocytosis: Toxic Effect of Amodiaquine in Bone Marrow Cultures In Vitro

Abstract: 1971; Slapak et al., 1971) and our own findings make it possible to construct a probable sequence of events in the hyperacute rejection process. The first change appears to be damage to the capillary endothelium presumably by an antibody antigen complex with subsequent binding of complement. This is followed by platelets adhering to the damaged endothelium and subsequent aggregation in the glomerular and peritubular capillaries. Substances released from these damaged platelets could result in the intense vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 8 publications
1
53
0
1
Order By: Relevance
“…The literature search revealed two postulated mechanisms by which amodiaquine can cause agranulocytosis:the first being dose dependent inhibitory effect on myeloid precursors [14] and second, an immune phenomenon attributed to anti IgG anti-neutrophil antibodies detected in the sera of the patients that were treated with amodiaquine and later developed agranulocytosis [15]. What really led to this extreme degree of agranulocytosis in our patient remains highly speculative.…”
Section: Discussionmentioning
confidence: 91%
“…The literature search revealed two postulated mechanisms by which amodiaquine can cause agranulocytosis:the first being dose dependent inhibitory effect on myeloid precursors [14] and second, an immune phenomenon attributed to anti IgG anti-neutrophil antibodies detected in the sera of the patients that were treated with amodiaquine and later developed agranulocytosis [15]. What really led to this extreme degree of agranulocytosis in our patient remains highly speculative.…”
Section: Discussionmentioning
confidence: 91%
“…The mechanism of agranulocytosis associated with the prophylactic use of AQ in man is unknown, though earlier investigations (Lind et al, 1973;Rhodes et al, 1986) suggested that an abnormal sensitivity of myeloid precursors to AQ might predispose individuals to this type of reaction. Inter-individual variation in drug disposition and drug-induced responses of the immune system might also play a role (Young & Vincent, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Cells from patients recovering from AQ-induced agranulocytosis, but not those obtained from healthy control subjects, displayed significant inhibition of colony formation with Correspondence: Dr J. W. Coleman, Department of Pharmacology and Therapeutics, University of Liverpool, Liverpool, L69 3BX AQ at 0.05-0.5 ,ug ml-' (approximately 0.1-1.0 ,umol 1-1). This suggested that patients had developed agranulocytosis as a result of abnormal sensitivity of their myeloid precursors to the drug, and that the myelosuppression was dosedependent and not idiosyncratic (Lind et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, the clinical use of AQ has been severely restricted because of the hepatoxicity and agranulocytosis side effects associated with its long term use. 4,5 Recent reports indicate that AQ was metabolized by cytochrome P-450 oxidation to form reactive quinoneimine metabolite with subsequent conjugate addition of glutathione or cysteinyl function of the enzymes. 6,7 Lysosomal accumulation and bioactivation of reactive quinoneimine metabolite are implicated to be the cause of the observed AQ in vivo toxicity.…”
Section: Introductionmentioning
confidence: 99%